2022
DOI: 10.3390/ani12070916
|View full text |Cite
|
Sign up to set email alerts
|

G0S2 Gene Polymorphism and Its Relationship with Carcass Traits in Chicken

Abstract: Gene single nucleotide polymorphisms can be used as auxiliary markers in molecular breeding and are an effective method to improve production performance. G0S2 is a key gene involved in regulating fat metabolism, but little research has been conducted on this gene regarding its role in poultry. In this study, the specialized commercial partridge chicken strain G0S2 gene was cloned and sequenced, and the relationship between the SNP sites on G0S2 and the carcass traits of chickens was investigated. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Promoting muscle development and reducing fat deposition are the top priority in chicken breeding ( Guo et al, 2019 ). Therefore, many studies have been devoted to exploring the potential candidate genes, regulatory network, and molecular mechanism to improve chicken carcass traits ( Li et al, 2015 ; Allais et al, 2019 ; Fu et al, 2020 ; Zhang et al, 2020 ; Wang et al, 2021 ; Li et al, 2022 ; Yang et al, 2022 ). However, it still needs further research to unravel the underlying mechanisms of chicken carcass traits.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting muscle development and reducing fat deposition are the top priority in chicken breeding ( Guo et al, 2019 ). Therefore, many studies have been devoted to exploring the potential candidate genes, regulatory network, and molecular mechanism to improve chicken carcass traits ( Li et al, 2015 ; Allais et al, 2019 ; Fu et al, 2020 ; Zhang et al, 2020 ; Wang et al, 2021 ; Li et al, 2022 ; Yang et al, 2022 ). However, it still needs further research to unravel the underlying mechanisms of chicken carcass traits.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [24] conducted InDel detection and association analysis in seven Chinese sheep breeds, revealing a significant association between GHR-InDel and growth traits (p < 0.05). Yang et al [25] found significant associations between seven SNPs (g.102G > A, g.255G > A, g.349C > T, g.384A > G, g.386G > A, g.444G > A, g.556G > A) of G0S2 and carcass traits in chickens. Specifically, individuals with the AG genotype at g.444G > A exhibited the highest breast muscle weight, while individuals with the AA genotype at g.556G > A showed the lowest fat weight (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high polymorphism and wide distribution of SNPs in the genome, they are widely used in genetic research, disease association studies and the resolution of individual differences ( Sachidanandam et al, 2001 ). Marker-assisted selection ( MAS ) has been widely used for selection and breeding of chickens for carcass traits ( Yang et al, 2022 ; Zhao et al, 2023 ; Zhou et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%